Ethanol Activation of Protein Kinase A Regulates GABAA Receptor Subunit Expression in the Cerebral Cortex and Contributes to Ethanol-Induced Hypnosis - Kumar, Sandeep; Ren, Qinglu; Beckley, Jonathan; O'Buckley, Todd; Gigante, Eduardo; Santerre, Jessica; Werner, David F.; Morrow, A Leslie (Frontiers in Neuroscience, 2012)
Protein kinases are implicated in neuronal cell functions such as modulation of ion channel function, trafficking and synaptic excitability. Both protein kinase C (PKC) and A (PKA) are involved in regulation of γ-aminobutyric acid type A (GABA-A) receptors through phosphorylation. However, the role of PKA in regulating GABA-A receptors following acute ethanol exposure is not known. The present study investigated the role of PKA in ethanol effects on GABA-A receptor α1 subunit expression in the P2 synaptosomal fraction of the rat cerebral cortex. Additionally, GABA-related behaviors were also examined. Rats were administered ethanol (2.0 – 3.5 g/kg) or saline and PKC, PKA and GABA-A receptor α1 subunit levels were measured by Western blot analysis. Ethanol (3.5 g/kg) transiently increased GABA-A receptor α1 subunit expression and PKA RIIβ subunit expression at similar time points whereas PKA RIIα was increased at later time points. In contrast, PKC isoform expression remained unchanged. Notably, the moderate ethanol dose (2.0g/kg) had no effect on GABA-A α1 subunit levels although PKA RIIα and RIIβ were increased at 10 and 60 minutes, when PKC isozymes are also known to be elevated. To determine if PKA activation was responsible for the ethanol-induced elevation of GABA-A α1 subunits, the PKA antagonist H89 was administered to rats prior to ethanol exposure. H89 administration prevented ethanol-induced increases in GABA-A receptor α1 subunit expression. Moreover, increasing PKA activity intracerebroventricularly with Sp-cAMP prior to a hypnotic dose of ethanol increased ethanol-induced loss of righting reflex duration. This effect appears to be mediated in part by GABA-A receptors as increasing PKA activity also increased the duration of muscimol-induced loss of righting reflex. Overall these data suggest that PKA mediates ethanol-induced GABA-A receptor expression and contributes to ethanol behavioral effects involving GABA-A receptors.